1978
DOI: 10.1111/j.1432-1033.1978.tb12168.x
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of the Active‐Site Cysteine Residue of Papain into a Dehydro‐serine, a Serine and a Glycine Residue

Abstract: Photolysis of papain which had been inhibited with 2-bromo-2',4'-dimethoxyacetophenone regenerated papain, but also formed [ A Ser2j ]papain (i.e. papain in which the active-site cysteine Kinetic specificity or the manifestation of enzyme specificity in the maximum velocity is a frequently encountered phenomenon in enzymology [I]. It is not explicable in terms of a simple structural complementarity between enzyme and substrate [2] and several alternative concepts have been suggested [3 -61. In order to gain a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

1984
1984
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 34 publications
(11 reference statements)
0
26
0
3
Order By: Relevance
“…Importantly, gene disruption studies in P. falciparum have shown that only SERA5 (“Ser”-type) and the much less abundant SERA6 (“Cys”-type: P. falciparum 3D7 PlasmoDB ID PF3D7_0207500) are essential in asexual blood stages (12, 20). Experimental Cys to Ser substitution at the active site of a number of cysteine proteases, including papain (21), streptopain (22), and cathepsin L (23), abolishes or profoundly reduces the proteolytic activity of those enzymes, so the absence of a catalytic Cys in SERA5 has led to suggestions that it and the other Ser-type SERAs are unlikely to be proteases. In support of this, only very limited protease activity was found associated with a recombinant form of the SERA5 papain-like domain (24), and x-ray crystallographic studies of the same protein have revealed aberrant structural features that cast doubt on its capacity to interact in a canonical manner with polypeptide substrates (25).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, gene disruption studies in P. falciparum have shown that only SERA5 (“Ser”-type) and the much less abundant SERA6 (“Cys”-type: P. falciparum 3D7 PlasmoDB ID PF3D7_0207500) are essential in asexual blood stages (12, 20). Experimental Cys to Ser substitution at the active site of a number of cysteine proteases, including papain (21), streptopain (22), and cathepsin L (23), abolishes or profoundly reduces the proteolytic activity of those enzymes, so the absence of a catalytic Cys in SERA5 has led to suggestions that it and the other Ser-type SERAs are unlikely to be proteases. In support of this, only very limited protease activity was found associated with a recombinant form of the SERA5 papain-like domain (24), and x-ray crystallographic studies of the same protein have revealed aberrant structural features that cast doubt on its capacity to interact in a canonical manner with polypeptide substrates (25).…”
Section: Introductionmentioning
confidence: 99%
“…Conversion of the papain active site cysteine residue to serine (as with the calpain C105S mutant) caused loss of activity, which was attributed to a difference in length between a C-O and C-S bond [15,16]. This may not however be the only factor involved.…”
Section: Discussionmentioning
confidence: 99%
“…Chalker et al [37] carried out chemical modification of cystein molecule using keratinous protein lately in 2009. Whereas, in 1978, Clark and Lowe [38] had already worked on conversion of the active-site cysteine residue of papain into a dehydro-serine, a serine and a glycine Residue. They used bromoacetophenone derivatives to alkylate cysteine of keratin and converted into formyl glycine photochemically.…”
Section: Keratin Modificationmentioning
confidence: 99%